2014
DOI: 10.1111/luts.12077
|View full text |Cite
|
Sign up to set email alerts
|

Study on Physiological Roles of Stimulation of Prostaglandin E2 Receptor Subtype EP2 in Urethral Function in Rats

Abstract: Taken together, these results suggest that stimulation of EP2 receptors induces relaxation likely via activation of cAMP-dependent mechanisms in rat urethral tissue, leading to a reduction of UPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
3
6
0
Order By: Relevance
“…CP‐533,536 has been reported as a selective EP2 receptor agonist with high affinity for the rat EP2 receptor with an IC 50 value of 50 nmol/L and 50‐fold more selectivity for EP2 than other PGE 2 ‐acting receptors, EP1, EP3 or EP4 . We previously reported that CP‐533,536 induces relaxation in rat urethral tissues pre‐contracted with the α 1 ‐adrenoceptor agonist phenylephrine . The present study showed that CP‐533,536 decreases UPP elevated by midodrine in rats.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…CP‐533,536 has been reported as a selective EP2 receptor agonist with high affinity for the rat EP2 receptor with an IC 50 value of 50 nmol/L and 50‐fold more selectivity for EP2 than other PGE 2 ‐acting receptors, EP1, EP3 or EP4 . We previously reported that CP‐533,536 induces relaxation in rat urethral tissues pre‐contracted with the α 1 ‐adrenoceptor agonist phenylephrine . The present study showed that CP‐533,536 decreases UPP elevated by midodrine in rats.…”
Section: Discussionsupporting
confidence: 61%
“…14 We previously reported that CP-533,536 induces relaxation in rat urethral tissues pre-contracted with the α 1 -adrenoceptor agonist phenylephrine. 15 The present study showed that CP-533,536 decreases UPP elevated by midodrine in rats. Taken together, these findings suggest that a selective EP2 receptor agonist might decrease UPP by relieving urethral constriction caused by stimulation of α 1adrenoceptors.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Measurement of Urethral Perfusion Pressure. Urethral perfusion pressure (UPP) was measured according to a previously described method (Kurihara et al, 2016). In brief, female Wistar rats (Charles River Laboratories Japan Inc.) were anesthetized with an intraperitoneal injection of urethane (1.2 g/kg) and fixed in the supine position.…”
Section: Methodsmentioning
confidence: 99%
“…The UPP in anesthetized rats was recorded continuously by infusing saline into the urethra at a rate of 4.5 mL/h. Following a stabilization period, UPP was measured in young and aged rats after intravenous administration of phenylephrine (0.03 mg/kg), which has been reported to elevate phenylephrine‐induced UPP . Changes in UPP (Δmm Hg) were calculated by subtracting baseline UPP just before phenylephrine administration from maximum UPP after phenylephrine (0.03 mg/kg, i.v.)…”
Section: Methodsmentioning
confidence: 99%